Analogies of Coding Systems of DNA and Elementary Particles - Girgvliani, Ani; Gogberashvili, Merab (Journal of Informatics and Mathematical Sciences, 2025)
We suggest that physical reality can be described in the language of division algebras, which dictates that their symmetries must be manifested in the coding systems of different structures of nature. We compare the structures of DNA and fundamental fermions. In both cases we observe (3+4)-element divisions which may arise from the symmetries of the 8-dimensional normed split-algebra. The analogies between the genetic code (given by codons that contain three nucleotide bases) and the properties of the structures of all possible baryons (quark triplets) are discussed. In the genetic code we have the degeneracy of codons built by four standard nucleotides that specify 21 amino acids in humans. Similarly, there are 21 major types of baryons built by four lightest quarks with the degeneration of their spin values. These analogies can help to address some unsolved problems in genetics and physics, like the origin of codon degeneracy, the fermion generation problem and structure of atomic nuclei.